Performance analysis of AMP for mobility management - Hassan, Wan H.; A-Hashim, Aisha H.; Fisal, Norsheila (2008)

(untitled)
In our previous work [1], a mechanism for handling movement detection using a proposed agent-based architecture for mobility mana gement was described. This architecture, referred here as AMP - Agent-bas ed Mobility Protocol, consists of a collaborative multi-agent system that enhances user/node mobility over an IP-based network. Specifically, mobility ag ents are placed in the hosts and at the access networks to expedite location and call management requirements. State information of mobile hosts (e. g. location and mobility profile) are relayed to the relevant agents who, in turn, will undertake appropriate tasks to ensure a smooth handover to th e next cell(s) during an on- going application session with minimum delay. In th is paper, the performance of the AMP architecture and protocol is examined using derived analytical models. Mobile QoS (Quality of Service) may be defined by signaling traffic overhead, handoff latency and packet loss. A comparative ana lysis is made between the AMP architecture and the IETF’s standard mobility m anagement protocol i.e. Mobile IPv6 .